2014
DOI: 10.12965/jer.140102
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill exercise alleviates impairment of spatial learning ability through enhancing cell proliferation in the streptozotocin-induced Alzheimer’s disease rats

Abstract: Alzheimer’s disease is the most common cause of dementia. This disease is a progressive and irreversible brain disorder accompanied with severe learning and memory impairment. Exercise increases cognitive ability, attenuates motor deficits, increases new neuron formation, and ameliorates neurological impairments in several neurodegenerative diseases. This study investigated the effects of treadmill exercise on spatial learning ability in relation with cell proliferation in the hippocampus. The rat model of Alz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Exercise improves cognitive and motor task performance (e.g. Leggio et al, 2005; Sim, 2014), and increases expression of neurotrophic factors (e.g. BDNF) (Turner & Lewis, 2003; Berchtold et al, 2010; Sim, 2014), hippocampal neurogenesis (van Praag, 2009; e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise improves cognitive and motor task performance (e.g. Leggio et al, 2005; Sim, 2014), and increases expression of neurotrophic factors (e.g. BDNF) (Turner & Lewis, 2003; Berchtold et al, 2010; Sim, 2014), hippocampal neurogenesis (van Praag, 2009; e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our study, the several reports have demonstrated that the sham+Ex group exerted no significant effect on the number of error choice in the radial 8-arm maze test as compared to the sham group. However, treadmill exercise enhanced BDNF and TrkB expressions in the hippocampus of rats (Sim, 2014). Many studies have shown that treadmill exercise in young normal animals exerted no significant effect on spatial learning and memory and short-term memory in the radial 8-arm maze and step-down avoidance tests (Heo et al, 2014; Kim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…AD was induced according to the previously described method (Jee et al, 2008; Sim, 2014). The rats were anesthetized with Zoletil 50 (10 mg/kg, intraperitoneally; Vibac Laboratories, Carros, France) and placed in a stereotaxic frame.…”
Section: Methodsmentioning
confidence: 99%
“…Alzheimer disease (AD) gradually impairs learning ability and memory function (Sim, 2014), and the incidence of AD is 50%–80% of dementia cases. The exact pathogenesis of AD is still not known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation